Analisis Makro Ekonomi Kabupaten Pohuwato - Ali, Sulha; Mardiana, Andi (LP2M IAIN Sultan Amai Gorontalo, 2020)
The macroeconomic indicators used as the basis for planning and evaluation for the development process in Pohuwato Regency are economic growth, inflation, TPAK, open unemployment, poverty levels, HDI, Gini ratio, ICOR, consumption growth, investment growth, and growth in government spending. Output multiplier and sectoral inequality. One indicator of the level of prosperity of the population in an area / region can be seen from the per capita GRDP value, which is the quotient between the added value generated by all economic activities and the population. Therefore, the size of the population will affect the value of PDRB per capita, while the size of the value of GRDP is highly dependent on the potential of natural resources and production factors in the area. PDRB per capita based on current prices shows the value of PDRB per head or per one population. Pohuwato's PDRB per capita value at the prevailing price from 2015 to 2019 has always increased. In 2015 the per capita GRDP was recorded at 31.11 million rupiah. In nominal terms, it continues to increase until 2019 reaching 41.04 million rupiah.